Factors Determining Purchasing Decisions: A Review of Social Media, E-WOM, and Product Quality - Wahyuningsih, Septia Tri; Hidayah, Arini; Miftahuddin, Muchammad Agung; Rahmawati, Ika Yustina (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyse the influence of social media, e-WOM, and product quality on purchasing decisions among consumers of Donlight Donut Shop. This study uses a quantitative method with data collection through questionnaires distributed directly. Non-probability sampling was used with the accidental sampling method, involving 110 respondents. Data analysis was assisted by SPSS 20. The results of the study indicate that social media, e-WOM, and product quality have a significant positive influence on purchasing decisions. The findings of this study can assist Donlight in improving its operational strategies, particularly in social media, e-WOM, and product quality, to maintain consumer purchasing decisions and enhance competitiveness in the food business.